Worsening abdominal pain leading to false laparotomy: a case of acute intermittent porphyria - Farah, Tehreem; Batool, Hania; Ashraf, Nasir; Qayyum Abbasi, Fatima; Nasir, Aisha (Journal of the Pakistan Medical Association, 2024)
Acute intermittent porphyria (AIP), one of the most severe types of acute hepatic porphyria, is an autosomal dominant inherited disorder of heme biosynthesis. We present a case of a 16-year-old girl who presented with severe abdominal pain, subjected to a laparotomy and later developed seizures and other neurological manifestations. Initial investigations showed hyponatraemia. Magnetic Resonance Imaging of brain showed cerebritis. She underwent several investigations including an ultrasound of abdomen, a computed tomography scan of abdomen and pelvis, cerebrospinal fluid routine examination and culture, and autoimmune investigation which were found to be normal. HM urine porphobilinogen levels were found to be raised. The diagnosis was made based on investigation and clinical symptoms. AIP should be suspected when a patient presents with chronic abdominal pain and neurological symptoms. Keywords: Acute Intermittent Porphyria, false laparotomy, appendicitis, acute abdomen, hyponatremia, tonic-clonic seizures.